In Situ Fabrication of Cuprous Selenide Electrode via Selenization of Copper Current Collector for High‐Efficiency Potassium‐Ion and Sodium‐Ion Storage. Issue 5 (23rd December 2021) - Chen, Xi; Li, Malin; Wang, Shi‐Ping; Wang, Chunzhong; Shen, Zexiang; Bai, Fu‐Quan; Du, Fei
Abstract: Selenium‐based materials are considered as desirable candidates for potassium‐ion and sodium‐ion storage. Herein, an in situ fabrication method is developed to prepare an integrated cuprous selenide electrode by means of directly chemical selenization of the copper current collector with commercial selenium powder. Interestingly, only the electrolyte of 1 m potassium hexafluorophosphate dissolved in 1, 2‐dimethoxyethane with higher highest occupied molecular orbital energy and lower desolvation energy facilitates the formation of polyselenide intermediates and the further selenization of the copper current collector. Benefiting from the unique thin‐film‐like nanosheet morphology and the robust structural stability of the integrated electrode, the volume change and the loss of selenide species could be effectively restrained. Therefore, high performance is achieved in both potassium‐ion batteries (462 mA h g −1 at 2 A g −1 for 300 cycles) and sodium‐ion batteries (775 mA h g −1 at 2 A g −1 for 4000 cycles). The facile fabrication strategy paves a new direction for the design and preparation of high‐performance electrodes. Abstract : An in situ fabrication strategy is proposed to prepare the integrated Cu2 Se electrode through selenization of Cu current collector by commercial selenium powder in a specific electrolyte (1 m KPF6 in 1, 2‐dimethoxyethane). Benefiting from the thin‐film‐like nanosheet morphology and the robust structural stability, integrated Cu2 Se electrode displays superior potassium‐ and sodium‐ion storage performance.